Natural Polyelectrolyte in Waste Sludge Treatment - Muyibi, Suleyman Aremu; Megat Mohd Noor, Megat Johari; Oog, Ding Tai; Kai, Khor Woon (Universiti Putra Malaysia Press, 2001)
The study involved laboratory based investigations to determine the efficacy of a natural Polyelectrolyte, Muringa oleifera seeds as a waste sludge conditioner. Waste sludge samples are activated sludge from Taman Tun Dr. Ismail Waste water Treatment Plant, Kuala Lumpur, Malaysia. Muringa oleifera seed was applied as dry powder(shelled blended), solution(shelled blended) and solution(shelled blended oil extracted) . Results of the studies showed that Muringa oleifera improved the filterability of waste sludge up to 62 % in the optimum dosage range of 3000 to 6000mg/\. Sludge volume reduction of up to 65% was also achievable using gravity filtration compared to the control (no Muringa oleifera added). The specific cake resistance of sludge conditioned with Muringa oleifera averaged 2.5 x 10 12 m/kg at the optimum dosage of 4000mg/\. The shelled blended category applied in dry powder form performed the same as the solution of shelled blended but better than shelled blended oil extracted categories of Muringa oleifera. Vegetable oil from the shelled Muringa oleifera seed of up to 30% was obtained as a by product.